Palabras mayores. La necesidad de los estudios etarios en comunicación para un cambio social - Dra. Virginia GUARINOS,Dra. Raquel MEDINA, (Fonseca, Journal of Communication, 2023)
As part of Cultural Studies, Age/ing Studies in Communication is a quite recent academic discipline in Spain, Europe, and Latin America